Pengaruh Perilaku Organisasi Dalam Implementasi Sasaran Keselamatan Pasien Terhadap Asuhan Keperawatan Yang Aman - Ketut Pramaini; Ni Putu Nina Eka Lestari (Universitas Pendidikan Nasional, 2016)
This research was conducted in RSU Surya Husadha Jl. P. Serangan no. 7 Denpasarwhich aims to find influence of Organizational Behavior In Implementation of Patient SafetyGoals To The Safe Nursing Care. A population of 188 people, using stratified randomsampling technique proportioned obtained a sample of 120 respondents. Using quantitativemethods, data collection techniques such as questionnaire and data analysis with causalmodels - SEM (Structural Equation Model) using AMOS program (Analysis of MomentStructure) 22.From the analysis and discussion, could be concluded that: The influence of thepersonal knowledge, safety culture, organizational environment in implementation of patientsafety goals are positive and significant. The influence of safety culture, organizationalenvironment and the implementation of patient safety goals to safe nursing care are positiveand significant. To maintain hospital good image to the community, so the implementation ofpatient safety goals is a quality that must be put forward and improved to the safe nursingcare by increasing knowledge of human resources through education and trainingcontinuously, create an organizational environment always conducive and make safetyculture as a part of the culture of the organization.Keywords : Personal knowledge, safety culture, organizational environment,implementation of patient safety goals, and safe nursing